TELAAH TERHADAP PERLINDUNGAN HAK ASASI MANUSIA DALAM NEGARA HUKUM INDONESIA - Agus Widodo (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2014)
Human rights are the basic rights of every human being as a creature of God who have an equal footing with others. Human rights are rights which are reflected by the democratic constitutional state, which is one of the important elements of the state law is the protection of human rights. Indonesia as a country of law upholding human rights and ensure the rights of all citizens are equal before the law and government, and must uphold the rule of law and without any exception. Translation of human rights in the UUD is in addition also in various laws and regulations in force. Human rights set out in the UUD 1945 had been born first than the Declaration of Human Rights. UUD 1945 guarantees the rule of law, in the sense not only as a state of law in the formal sense or narrow, but also in the sense of material or in a broader sense.